The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/jnnp-2020-324903
|View full text |Cite
|
Sign up to set email alerts
|

Predicting loss of independence and mortality in frontotemporal lobar degeneration syndromes

Abstract: ObjectiveTo test the hypothesis that in syndromes associated with frontotemporal lobar degeneration, behavioural impairment predicts loss of functional independence and motor clinical features predict mortality, irrespective of diagnostic group.MethodsWe used a transdiagnostic approach to survival in an epidemiological cohort in the UK, testing the association between clinical features, independence and survival in patients with clinical diagnoses of behavioural variant frontotemporal dementia (bvFTD n=64), no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…A study published in 2021 reported that motor symptoms were associated with reduced survival in patients with frontotemporal degeneration, including parkinsonism, dystonia, and apraxia. 31 Besides, rapid eating and dysphagia are common in patients with frontotemporal degeneration, and these symptoms might increase the risk of choking, aspiration pneumonia, and mortality. 32 Importantly, people with frontotemporal degeneration might have a younger age at onset and diagnosis than people with Alzheimer's disease, and thereby the mortality rate after diagnosis might be attenuated during the followup period.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2021 reported that motor symptoms were associated with reduced survival in patients with frontotemporal degeneration, including parkinsonism, dystonia, and apraxia. 31 Besides, rapid eating and dysphagia are common in patients with frontotemporal degeneration, and these symptoms might increase the risk of choking, aspiration pneumonia, and mortality. 32 Importantly, people with frontotemporal degeneration might have a younger age at onset and diagnosis than people with Alzheimer's disease, and thereby the mortality rate after diagnosis might be attenuated during the followup period.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PSP often display prominent neuropsychiatric problems, including apathy and impulsivity [2][3][4] . In PSP and related disorders, apathy and impulsivity reduce survival 5 and predict loss of functional independence 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the consequences is an impairment of response inhibition, contributing to disinhibited behaviour and impulsivity. These are associated with poor clinical outcomes [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the consequences is an impairment of response inhibition, contributing to disinhibited behaviour and impulsivity. These are associated with poor clinical outcomes 4-6 . Impulsivity is a multi-faceted behavioural construct, including abnormal sensitivity to reward, intolerance to delayed reward and a failure to inhibit inappropriate responses 7,8 .…”
Section: Introductionmentioning
confidence: 99%